Professional legal for non-legal for higher education sector (ProLeNoL) - Wan Zahari, Wan Mohd. Zulhafiz (Akademi Kepimpinan Pendidikan Tinggi, 2023)
Good governance and proper administration play significant roles to ensure the efficient and effective management of any institutions, including universities. In this regard, university authorities must be endowed with the legal knowledge pertinent to their scope of work. It will enable them to comprehend the policies, rules, laws, and regulations practised or implemented within their respective institution. In keeping with the spirit, the ProLeNol aims to improve the effectiveness of good governance and proper university administration by ensuring university administrators understand the applicable laws and enhancing participants' understanding of accountability and liability under relevant law and legislation. To accomplish the objective, as well as considering the non-legal backgrounds of the participants, the modules have been designed to include both the fundamental and practical aspects of the law that are relevant to universities. It begins with the first module, which discusses the pertinent laws and statutes that govern public universities and the legal and governance structure of public universities. The second module discusses the responsibilities and liabilities of university authorities and their role in accordance with applicable laws, which can be further divided into two parts. The first component of the discussion focuses on the duties and liabilities of university authorities and how they carry out as well as discharge their legal obligations and responsibilities, with reference to the company law. The second part of the discussion explains the duties and liabilities of university authorities through the lens of administrative law, amongst others, the legal principles governing the administrative apparatus, discretionary power, the doctrine of exceeding power, administrative adjudication, natural justice, and available legal remedies, such as habeas corpus, mandamus, certiorari, quo warranto, declaration, injunction, and damages. To minimise the legal exposures and detrimental liability to be borne by the university, the third module discusses the application of university-related cases through court decisions and precedents concerning the operation and administration of university. The final module discusses the legal context of sustainable governance, including university's sustainable governance, university's sustainable ecosystem, and enhancing board effectiveness. With the above exposures, it is hoped that university administrators will better understand the accountability and liability of each department, office, or institution under their management. In addition, the programme will equip the administrators with the necessary legal knowledge to enhance their application and consideration of applicable laws during dayto-day operations and decision-making at the university.